EFEKTIVITAS METODE EXAMPLE NON-EXAMPLE BERBANTUAN FOTO DALAM PENINGKATAN KEMAMPUAN MENULIS TEKS PERSUASI - Putri, Jasmine Primasari; Suntoko, Suntoko; Hartati, Dian (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study describes the application of the Example Non-Example method through the use of photo media in improving persuasive text writing skills in VIII students of SMPN 3 Cibarusah. This research uses a quantitative quasi-experiment approach with a nonequivalent control group design. Data collection in this study was carried out using observation, interview, test, and documentation techniques. The data came from the results of the initial and final tests, which were tested through normality, homogeneity, n-gain, and hypothesis testing. The results showed that there was an increase between the results of the initial test and the final test. The increase was evidenced through the acquisition of the average value of the treatment from 79.83 to 86.33. The n-gain test results prove that the application of the Example Non-Example method assisted by photo media in improving the ability to write persuasive text is considered effective.